2003
DOI: 10.1051/0004-6361:20031613
|View full text |Cite
|
Sign up to set email alerts
|

Anomalously bright UV lines of Fe II as a probe of gas condensations in the vicinity of hot stars

Abstract: Abstract. Two UV lines of Fe II at 2507/2509 Å are extremely bright in spatially resolved HST/STIS spectra of dense gas condensations (the so called Weigelt blobs) close to the central star of η Carinae. The lines also appear unresolved in HST/FOS spectra of the star AE And. Under normal conditions the lines should hardly be observable. Based on recent studies of the formation of the λλ2507/2509 lines as part of a radiative cycle driven by HLyα pumping and including stimulated emission we propose the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…They all respond strongly to changes in the Lyα flux. This group includes permitted lines of Fe II, Fe III, Ni II, and Cr II, especially noteworthy are the famous Fe II lines, λλ2507 and 2509, demonstrated to be pumped by Lyα (Figure 4; Johansson & Letokhov 2003;and references therein). The intensities of Fe II λλ2507, 2509 increased about 2.5-fold in the eleven month interval between the 1998 and 1999 observations.…”
Section: Changes In Line Intensitiesmentioning
confidence: 99%
“…They all respond strongly to changes in the Lyα flux. This group includes permitted lines of Fe II, Fe III, Ni II, and Cr II, especially noteworthy are the famous Fe II lines, λλ2507 and 2509, demonstrated to be pumped by Lyα (Figure 4; Johansson & Letokhov 2003;and references therein). The intensities of Fe II λλ2507, 2509 increased about 2.5-fold in the eleven month interval between the 1998 and 1999 observations.…”
Section: Changes In Line Intensitiesmentioning
confidence: 99%
“…The most prominent nebular features from the Weigelt condensations during η Car's spectroscopic high-state are the H I Lyα-pumped fluorescent lines in Fe II, especially Fe II λλ2507, 2509 (Johansson & Letokhov 2003). Transitions from higher ionization stages, such as Fe 2+ , Fe 3+ , Ne 2+ , were also identified in the spectrum.…”
Section: The η Car Spectrummentioning
confidence: 94%
“…One particular problem (Johansson & Letokhov 2003) was the understanding of why the kk2507, 2509 lines are so strong in the observed spectrum, and why they are of approximately equal strength. Verner et al (2002) found that if they abandoned the atomic data already published at that time and assumed a 50% mixing of the two upper levels of these transitions, their model did indeed agree with observation that these two lines are the strongest in the spectrum and of comparable intensity.…”
Section: Introductionmentioning
confidence: 99%